BILINGVAL TEZAURUS YARATISHDA O ‘ZBEK VA INGLIZ TILLARINING VALENTLIK MUNOSABATI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Thesaurus is a database created for the analysis of dictionaries, words and their interactions. They are a special set of related words. The main purpose of these dictionaries is to find other words in the meaning of a word and to find similar words. This thesis discusses the valence relations of Uzbek and English languages in creating a thesaurus, a bilingual thesaurus.
Keywords: actant, argument, bilingual thesaurus, valence relation, valency, thesaurus, linguistics.